Preservation of the Batik Industry in Indonesia as Part of the National Identity - Lilam Kadarin Nuriyanto (International Journal of Science and Applied Science: Conference Series, 2022)
Culture in general can be interpreted as matters relating to the human mind. Culture is the identity or characteristic of a nation as a differentiator with other nations. Identity becomes the pride and even the main attraction of a nation. One of the cultures owned by the Indonesian people is batik which is the result of a combination of art and technology. Various kinds of batik philosophically and meaningfully will be found in various customs and cultures that develop in Indonesia. Indonesia has several batik motifs related to local culture. Several factors that influence the birth of batik motifs include geographical location. This paper aims to find out how efforts are being made to preserve the batik industry in Indonesia. Data collection techniques using library methods related to various matters relating to batik culture. Some of these findings include the development of a promotion system to increase sales, and efforts to regenerate batik experts carried out by business actors with the assistance of programs from the government.